2021
DOI: 10.3390/ijms22031120
|View full text |Cite
|
Sign up to set email alerts
|

PEG Linker Length Strongly Affects Tumor Cell Killing by PEGylated Carbonic Anhydrase Inhibitors in Hypoxic Carcinomas Expressing Carbonic Anhydrase IX

Abstract: Hypoxic tumors overexpress membrane-bound isozymes of carbonic anhydrase (CA) CA IX and CA XII, which play key roles in tumor pH homeostasis under hypoxia. Selective inhibition of these CA isozymes has the potential to generate pH imbalances that can lead to tumor cell death. Since these isozymes are dimeric, we designed a series of bifunctional PEGylated CA inhibitors (CAIs) through the attachment of our preoptimized CAI warhead 1,3,4-thiadiazole-2-sulfonamide to polyethylene glycol (PEG) backbones with lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…Long-term cytotoxicity study showed ( Figure 2 c) that after treatment with FA 2 -dPEG-DOX 2 at 100 μM concentration (regarding DOX), viability values of the treated MDA-MB-231 cells were similar to the untreated control until 48 h. However, treatment with FA 2 -dPEG-DOX 2 reduced cell viability significantly after 48 h (compared to the control) and sustained at an approximately constant level for 168 h. The results show slow DOX release in the cell culture medium investigated. Similar studies often do not investigate simulated drug release profiles because they may not be predictive for in vivo conditions [ 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term cytotoxicity study showed ( Figure 2 c) that after treatment with FA 2 -dPEG-DOX 2 at 100 μM concentration (regarding DOX), viability values of the treated MDA-MB-231 cells were similar to the untreated control until 48 h. However, treatment with FA 2 -dPEG-DOX 2 reduced cell viability significantly after 48 h (compared to the control) and sustained at an approximately constant level for 168 h. The results show slow DOX release in the cell culture medium investigated. Similar studies often do not investigate simulated drug release profiles because they may not be predictive for in vivo conditions [ 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…PDCs. Research carried out with various polymers, including PEG, showed promise due to increased water solubility and circulation time in the body, and multivalent attachment to receptors FR [ 15 , 16 , 17 , 18 , 19 , 20 ]. Despite the progress achieved in the field, several obstacles currently impede the clinical translation of PDC-based therapeutics [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Each inhibitor concentration was tested in triplicate, and the reported values represent the mean of these results. The inhibition constants were calculated using nonlinear least‐squares methods, employing the Cheng‐Prusoff equation, as previously reported, and are the average of at least three separate determinations [43–53] …”
Section: Methodsmentioning
confidence: 99%
“…The inhibition constants were calculated using nonlinear least-squares methods, employing the Cheng-Prusoff equation, as previously reported, and are the average of at least three separate determinations. [43][44][45][46][47][48][49][50][51][52][53] . All CA isozymes used in this study were recombinant proteins previously obtained by our research group.…”
Section: Ca Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation